Katalyst: development of a fifth-grade novel approach to health and science experiential learning. (2nd October 2018) - Baker, Kathryn; Hagedorn, Rebecca L.; Hendricks, Tyler; Clegg, Emily N.; Joseph, Lauren; McGowan, Melissa; Olfert, Melissa D.
Abstract: The Katalyst intervention program was piloted in fifth-grade classrooms at two Appalachian schools during the 2017–18 academic year as a potential educational resource to tackle the rising rates of obesity and chronic diseases in this region. The program consisted of four 60-minute modules, each based on a specific organ system. Each module incorporated hands-on lessons in physiology with an emphasis on preventing chronic disease through diet, nutrition, physical activity, and abstinence from drug and tobacco use. The modules were led by medical students and undergraduate volunteers who completed a two-day training. A 37-item survey assessing knowledge and perceptions regarding healthy lifestyles was administered to fifth grade participants prior to and following the intervention in order to assess the impact of the program. Additionally, educators at intervention schools were given a questionnaire post-intervention to provide feedback on the program. This paper describes the rationale, program design and execution, and conclusion of the Katalyst intervention program. It is anticipated that this program will reinforce current educational standards regarding diet, nutrition and physical activity in order to empower target students to establish healthy lifestyle behaviors and that programs modeled after the Katalyst curriculum may serve as a novel, viable option to health educators.